2023
DOI: 10.3390/ani13101607
|View full text |Cite
|
Sign up to set email alerts
|

Development of Forensically Important Sarcophaga peregrina (Diptera: Sarcophagidae) and Intra-Puparial Age Estimation Utilizing Multiple Methods at Constant and Fluctuating Temperatures

Abstract: Sarcophaga peregrina (Robineau-Desvoidy, 1830) has the potential to estimate the minimum postmortem interval (PMImin). Development data and intra-puparial age estimation are significant for PMImin estimation. Previous research has focused on constant temperatures, although fluctuating temperatures are a more real scenario at a crime scene. The current study examined the growth patterns of S. peregrina under constant (25.75 °C) and fluctuating temperatures (18–36 °C; 22–30 °C). Furthermore, differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Sarcophaga africa had a slow life cycle, with a 1.66-day difference between the rainy and winter seasons and a rapid one during the summer [33]. Shang et al found that, under fluctuating temperatures (18-36 • C and 22-30 • C), S. peregrina had a longer development and a lower pupariation rate and emergence rate than those observed at constant temperatures [34]. Some discrepancy was observed in the growth rates of insects maintained under controlled laboratory conditions with a constant temperature and those subjected to variable temperatures in their natural habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcophaga africa had a slow life cycle, with a 1.66-day difference between the rainy and winter seasons and a rapid one during the summer [33]. Shang et al found that, under fluctuating temperatures (18-36 • C and 22-30 • C), S. peregrina had a longer development and a lower pupariation rate and emergence rate than those observed at constant temperatures [34]. Some discrepancy was observed in the growth rates of insects maintained under controlled laboratory conditions with a constant temperature and those subjected to variable temperatures in their natural habitat.…”
Section: Introductionmentioning
confidence: 99%